Predictors of Intention and Behavior of Digital Banking Service Users in the Islamic Banking Industry - Suci Mulyati; Ahyar Ahyar; Samsiar Samsiar; Ilza Febrina; Nurkamariah Nurkamariah; Syafwan Syafwan (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, the adoption of Islamic digital banking is driven by technical infrastructure, ease of access, and optimal price-value matching for customers. However, in reality, the determinants of digital adoption in Islamic banking often shift from mere technical functions to specific psychological aspects, habits, and religious values that have not been fully mapped. This study aims to analyze the predictors of user intentions and behavior of digital banking services in the Islamic banking industry by developing an expanded UTAUT3 model through the integration of personal innovativeness and Islamic lifestyle as moderating variables. A quantitative approach was employed using SEM-PLS through SmartPLS 3.0, involving 266 digital banking customers of Islamic banks across Indonesia. The findings reveal that user motivation, habit, and personal innovativeness significantly influence behavioral intention, while habit also affects actual user behavior. In contrast, performance expectancy, effort expectancy, social influence, facilitating conditions, and price value show no significant effects. Islamic lifestyle was found to strengthen social influence on behavioral intention, but it did not moderate the relationship between habit and intention. This research contributes to the theoretical expansion of the UTAUT3 model through the integration of Islamic lifestyle and personal innovativeness variables, while also providing practical recommendations for Islamic banking management to focus on cultural value-based marketing strategies and the formation of customers' digital habits.